A cross‐sectional analysis of Kenyan postabortion care services using a nationally representative sample. Issue 3 (6th July 2017) - Mutua, Michael M.; Achia, Thomas N.O.; Maina, Beatrice W.; Izugbara, Chimaraoke O.
Abstract: Objective: To assess quality of postabortion care (PAC) offered by Kenyan healthcare facilities. Methods: A cross‐sectional survey was conducted using data from the Incidence and Magnitude of Unsafe Abortions study, conducted among 326 PAC‐providing healthcare facilities throughout Kenya from March 13 to June 30, 2012. Descriptive results with weighted proportions and an ordered probit model were used. Results: Overall, 408 (41.8%) first‐trimester PAC cases were treated using appropriate technology versus 826 (82.6%) second‐trimester cases. Private healthcare facilities lagged behind public healthcare facilities on the use of appropriate technology: 264 (47.5%) public and 144 (33.1%) private facilities used such technology for first‐trimester abortion, and 664 (89.6%) public versus 162 (68.8%) private for second‐trimester abortions). Most healthcare facilities (251, 70.7%) had at least one provider trained in PAC. A total of 273 (80.7%) healthcare facilities reported offering contraception to all PAC patients, mainly short‐acting methods. Delivery of PAC services depended on the availability of separate evacuation room (public level 2–3: odds ratio [OR] 22.93; public level 4–6: OR 77.14), and the number of family planning methods offered within the facility (public level 2–3: OR 1.38; public level 4–6 OR 1.57; private level 2–3: OR 2.27; private level 4–5: 4.89). Conclusion: Effective monitoring of PAC services, particularly among private healthcare facilities, might improve overall quality of services. Abstract : Improving capacity of level‐2 and level‐3 facilities to offer quality postabortion care through skill development, including effective family planning, enhances quality of services.